Modelagem, simulação e otimização de transformadores piezoelétricos de modo radial para aplicações em conversão de potência - Barros, Marcelo Henrique Martins de (Universidade Federal de São Carlos, 2008)
This work seeks to improve the modeling, analysis and the optimization of the parameters of piezoelectric transformer (PT) built with polarized Pb(Zr,Ti)O3 electro-ceramics for applications in power conversion, as well as to characterize them. The main motivation resides in the great similarity of the electric model of the PT in relation to the LC resonant tanks plus magnetic transformer commonly employees in AC/DC and DC/DC power converters. Such similarity could make possible its application in power conversion, with good energy efficiency, as well as reduction of volume, weight, complexity, cost and electromagnetic emission, when compared to the converters based on magnetic devices, that today dominate almost all the applications. The power conversion accomplished in way more and more rational and with low losses of energy it is, without a doubt, one of the great concern of our time, for the expressive economic and environment impacts. A PT is a electric device that combines an piezoelectric driver on the primary side with a piezoelectric receiver on the secondary side. Both can work with transverse or longitudinal vibration modes. These drivers and receivers are made of piezoelectric elements, being for its time composed of metal plates (electrodes) and of polarized electro-ceramics. To the likeness of the magnetic transformers, piezoelectric transformers are transmission devices of electric energy, even so accomplished through eletro-mechanic coupling between the driver and the receiver. They can be used in the function of insulators, reducers or elevators of the applied voltage on the primary side. Based on the piezoelectric and wave equations, the electric equivalent circuit of a piezoelectric transformer in radial-mode vibration was obtained and later on improved, starting from a more complete approach, including effects that are usually despised. A performance analysis was accomplished through computer simulation and it was explored the limits for the power rate transfer for thermal and electromechanics considerations. Later on an outline of optimization of the piezoelectric transformer in a radial-mode was traced, in order to maximize the efficiency and of adapting it to applications of power conversion; also through computer simulation. Since the electric equivalent circuit of a piezoelectric transformer is commonly identical to the LC resonant tanks used in power conversion in high frequency switch-mode resonant scheme, the PT can substitute the magnetic transformer, the indutor and the capacitor of the resonant tanks, as well as to increase the energy efficiency and to reduce significantly the number of devices, the volume, the cost and the electromagnetic emission of an application in power conversion.
Keywords: Eletricidade e eletrônicos; Transformadores elétricos; Conversão de potência; Cerâmicas ferroelétricas; CIENCIAS EXATAS E DA TERRA::FISICA